Compartmentalization of Gene Expression during Bacillus subtilis Spore Formation - Hilbert, David W. (American Society for Microbiology, 2004)
Gene expression in members of the family Bacillaceae becomes compartmentalized after the distinctive, asymmetrically located sporulation division. It involves complete compartmentalization of the activities of sporulation-specific sigma factors, σ(F) in the prespore and then σ(E) in the mother cell, and then later, following engulfment, σ(G) in the prespore and then σ(K) in the mother cell. The coupling of the activation of σ(F) to septation and σ(G) to engulfment is clear; the mechanisms are not. The σ factors provide the bare framework of compartment-specific gene expression. Within each σ regulon are several temporal classes of genes, and for key regulators, timing is critical. There are also complex intercompartmental regulatory signals. The determinants for σ(F) regulation are assembled before septation, but activation follows septation. Reversal of the anti-σ(F) activity of SpoIIAB is critical. Only the origin-proximal 30% of a chromosome is present in the prespore when first formed; it takes ≈15 min for the rest to be transferred. This transient genetic asymmetry is important for prespore-specific σ(F) activation. Activation of σ(E) requires σ(F) activity and occurs by cleavage of a prosequence. It must occur rapidly to prevent the formation of a second septum. σ(G) is formed only in the prespore. SpoIIAB can block σ(G) activity, but SpoIIAB control does not explain why σ(G) is activated only after engulfment. There is mother cell-specific excision of an insertion element in sigK and σ(E)-directed transcription of sigK, which encodes pro-σ(K). Activation requires removal of the prosequence following a σ(G)-directed signal from the prespore.